Liquidity, hedging and the survival of North German dairy farms. (16th February 2021) - Hoehl, Stephan; Hess, Sebastian
Abstract: Increasingly, European dairy farmers have to manage the raw milk price risk. Price hedging for raw milk and an increasing number of individual fixed-price contracts with processors are now available. However, the choice of hedging a certain share of milk output still leaves individual farmers facing a complex decision. The cash flow model in this study explains the probability of a typical northern European dairy farm surviving illiquidity over an 18-month period under common milk price volatility. The probability of farm survival was modelled in relation to available liquidity buffers and different levels of farm-specific production costs. The model allowed minimum shares of milk output to be determined, for which a fixed price should be hedged if the objective is farm survival at a given probability. Using these modelling results, practitioners are able to determine this share graphically.